Research On Crispy Chocolate Packaging - Lee, Suok Fung (Universiti Malaysia Sarawak, UNIMAS, 2007)
In an ever changing competitive business environment, packaging design plays an important role in marketing a product regardless of the type of business you are. The most important aspect of packaging is to project a high perceived value that people cannot resist but want to buy the product. Chocolate packaging has evolved tremendously over the years with quality materials, creative designs, interesting forms and functions with the use of advance technology. In order to compete in the global market, “Ovita” needs to position itself effectively to capture the young generation market segment. Positioning itself as a healthy, nutritious energy chocolate “Ovita” hopes to be a market leader and compete with other established brands and gain their market share in this business.